Perilaku Impulsive Buying Gen-Z dalam Perspektif Etika Bisnis Islam - Aminah, Aminah; Nurhasanah, Lisa (LABATILA : Jurnal Ilmu Ekonomi Islam, 2023)
Globalization is currently influencing people's consumption behavior. Society's tendency is towards irrational consumption behavior, namely impulsive buying. With the rapid development of internet technology, Generation-Z's shopping patterns have changed from initially shopping in stores to shopping online in marketplaces. This research aims to analyze impulsive buying consumption behavior and review Islamic business ethics on impulse buying consumption behavior carried out by generation-Z in the marketplace. With this type of field research and using quantitative methods, the data collection technique used is a survey by distributing questionnaires to 399 respondents in Cirebon district which is the sample in this research. The analysis method used is descriptive and tabulation. The results of this research show that the impulsive buying behavior carried out by the Z generation in Cirebon Regency is included in the suggestion impulsive buying type which is influenced by external factors, namely reviews or assessments of the product they want to buy. Apart from these external factors, impulsive buying behavior is also influenced by internal factors, including promotions; attractive product visuals; discount; and free shipping. Generation-Z's impulsive buying behavior from the perspective of Islamic business ethics has not been carried out optimally, especially from the principle of "responsibility". This is because most respondents have hit and run or canceled orders.